Antigen-presenting cancer associated fibroblasts enhance antitumor immunity and predict immunotherapy response - Junquan Song; Rongyuan Wei; Chenchen Liu; Zhenxiong Zhao; Xuanjun Liu; Yanong Wang; Fenglin Liu; Xiaowen Liu (Nature Communications)
Abstract Cancer-associated fibroblasts (CAF) play a crucial role in tumor progression and immune regulation. However, the functional heterogeneity of CAFs remains unclear. Here, we identify antigen-presenting CAFs (apCAF), characterized by high MHC II expression, in gastric cancer (GC) tumors and find that apCAFs are preferentially located near tertiary lymphoid structures. Both in vivo and in vitro experiments demonstrate that apCAFs promote T cell activation and enhances its cytotoxic and proliferative capacities, thereby strengthening T cell-mediated anti-tumor immunity. Additionally, apCAFs facilitate the polarization of macrophages toward a pro-inflammatory phenotype. These polarized macrophages, in turn, promote the formation of apCAFs, creating a positive feedback loop that amplifies anti-tumor immune responses. Notably, baseline tumors in immunotherapy responders across various cancer types exhibit higher levels of apCAFs infiltration. This study advances the understanding of CAFs heterogeneity in GC and highlights apCAFs as a potential biomarker for predicting immunotherapy response in pan-cancer.